MANAJEMEN LAYANAN PRIMER PENGENDALIAN PENYAKIT TIDAK MENULAR: LITERATURE REVIEW - Budiana, Irwan; Paschalia, Yustina; Doondori, Anatolia K. (Poltekkes Kemenkes Kupang, 2024)
Introduction: Unhealthy lifestyle changes increase the threat of increasing cases of death due to non-communicable diseases. Implementing effective primary care management can encourage the realization of a community movement to adopt a healthier lifestyle. This research aims to examine the implementation of primary care management, especially efforts to prevent and control NCDs. Method: Data collection is in the form of searching for articles via the Google Scholar electronic database published in 2014-2024 and using a foreign language (English) or Indonesian as an introduction. The literature search focused on primary care management, especially those related to the elements and functions of non-communicable disease control management. Results: Implementation of good primary service management requires support from various parties, especially leadership roles such as the use of a leadership style that suits the organizational climate. Commitment from the leadership or manager of the service center also influences the quality of primary services. This has an impact on the quality of services, including non-communicable disease control services. Conclusion: Management in the primary health care area plays a very important role in optimizing the utilization of all health resources in the context of controlling non-communicable diseases at all levels of society.